Teachers' and Students' Attitudes Toward the Use of Music in UAE English Language Classrooms - Hejjawi, Lina (2007)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) Submitted to the College of Arts and Sciences by Lina K. Hejjawi Entitled, "Teachers' and Students' Attitudes Toward the Use of Music in UAE English Language Classrooms," January 2007. Available are both Soft and Hard Copies of the Thesis.